Measurement of the nonlinear optical response of low-density lipoprotein solutions from patients with periodontitis before and after periodontal treatment: evaluation of cardiovascular risk markers - Monteiro, Andrea M.; Jardini, Maria Aparecida Neves [UNESP]; Giampaoli, Viviana; Alves, Sarah; Figueiredo Neto, Antonio M.; Gidlund, Magnus (Spie-soc Photo-optical Instrumentation Engineers, 2012)
The Z-Scan (ZS) technique in the thermal regime has been used to measure the nonlinear optical response of low-density lipoprotein (LDL). The ZS technique is carried out in LDL from 40 patients with chronic periodontitis before and after three, six, and 12 months of periodontal treatment. Clinical parameters such as probing depths, bleeding on probing, total and differential white blood cells counts, lipid profiles, cytokine levels, and antibodies against oxidized LDL are also determined and compared over time. Before the treatment, the ZS experimental results reveal that the LDL particles of these patients are heavily modified. Only after 12 months of the periodontal treatment, the ZS results obtained reveal behavioral characteristics of healthy particles. This conclusion is also supported by complementary laboratorial analysis showing that the periodontal treatment induces systemic changes in several inflammatory markers. (C) 2012 Society of Photo-Optical Instrumentation Engineers (SPIE). [DOI: 10.1117/1.JBO.17.11.115004]
Keywords: Z-scan; nonlinear; atherosclerosis; inflammation; oral health; oxLDL; periodontitis